2004
DOI: 10.1182/blood-2003-10-3717
|View full text |Cite
|
Sign up to set email alerts
|

Targeted retroviral transduction of c-kit+ hematopoietic cells using novel ligand display technology

Abstract: Gene therapy for a wide variety of disorders would be greatly enhanced by the development of vectors that could be targeted for gene delivery to specific populations of cells. We describe here high-efficiency targeted transduction based on a novel targeting strategy that exploits the ability of retroviruses to incorporate host cell proteins into the surface of the viral particle as they bud through the plasma membrane. Ecotropic retroviral particles produced in cells engineered to express the membrane-bound fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 32 publications
(47 reference statements)
1
24
0
Order By: Relevance
“…If a specific receptor is overexpressed on the cell membrane of a producer cell line, then this will also be displayed on the viral envelope. When overexpressing stem cell factor (SCF) on the cell membrane of an ecotropic producer cell line, Chandrashekran et al 135,136 showed that retrovirus thus produced was able to preferentially transduce c-kit expressing human stem cells. Recently, Yang et al 137 demonstrated that this approach can also be applied for lentiviruses.…”
Section: Toward Specific Targeting Of Dcs By In Vivo Lentiviral Vectomentioning
confidence: 99%
“…If a specific receptor is overexpressed on the cell membrane of a producer cell line, then this will also be displayed on the viral envelope. When overexpressing stem cell factor (SCF) on the cell membrane of an ecotropic producer cell line, Chandrashekran et al 135,136 showed that retrovirus thus produced was able to preferentially transduce c-kit expressing human stem cells. Recently, Yang et al 137 demonstrated that this approach can also be applied for lentiviruses.…”
Section: Toward Specific Targeting Of Dcs By In Vivo Lentiviral Vectomentioning
confidence: 99%
“…Moreover, vectors from different sources (2) and with alternative or reengineered targeting envelopes (3,21,33,40) may be particularly sensitive to centrifugation (35). Thus, magnetic concentration not only is a useful purification technology but also allows the use of additional factors for capture and/or targeting strategies that are not dependent on the modification of viral envelope proteins (7,8).…”
mentioning
confidence: 99%
“…To overcome these limitations, retroviral vectors have been extensively modified to generate self-inactivating vectors [70]. Further, packaging cell lines have been modified to attenu-future science group Modification of viral vectors by nanomaterials Review ate vector inactivation by serum complement [71] or to endow target-specificity to RVs [72], thus leading to enhanced safety and therapeutic profiles.…”
Section: Retrovirusesmentioning
confidence: 99%